1997
DOI: 10.2307/2952258
|View full text |Cite
|
Sign up to set email alerts
|

Politics Matters: Political Events as Catalysts for Preadult Socialization

Abstract: We propose that (1) the preadult socialization of longstanding, stable predispositions is catalyzed by exogenous political events; (2) such events socialize attitudes selectively, only in the specific domains they make salient; and so (3) longstanding predispositions tend to be socialized episodically rather than incrementally. This theory is applied to the socialization of partisanship during a presidential campaign, examining gains in information, affective expression, and attitude crystallization. Adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
256
1
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(277 citation statements)
references
References 44 publications
6
256
1
14
Order By: Relevance
“…The teachers' reports, student work, and our observations confirm that the students were passionately engaged in the campaign and aftermath. Learning about politics and social issues during early adolescence is vital because as people move from adolescence to adulthood, their political orientations tend to become more rigid (Osborne, Sears, & Journal of Education & Social Sciences Valentino, 2011;Reichert, 2016a;Sears & Valentino, 1997). Precisely when this crystallization of political orientations occurs is not known; however, our study demonstrates that 13-and 14-year-olds' political ideologies are quite malleable.…”
Section: Discussioncontrasting
confidence: 39%
“…The teachers' reports, student work, and our observations confirm that the students were passionately engaged in the campaign and aftermath. Learning about politics and social issues during early adolescence is vital because as people move from adolescence to adulthood, their political orientations tend to become more rigid (Osborne, Sears, & Journal of Education & Social Sciences Valentino, 2011;Reichert, 2016a;Sears & Valentino, 1997). Precisely when this crystallization of political orientations occurs is not known; however, our study demonstrates that 13-and 14-year-olds' political ideologies are quite malleable.…”
Section: Discussioncontrasting
confidence: 39%
“…2). As public opinion research has shown, while most citizens tend to form reasonably durable views about the political parties, presidential candidates, and issues involving morality, religion, and race relations, individual differences in attitude strength and stability across issues are prevalent (e.g., Alwin, Cohen, and Newcomb 1991;Converse and Markus 1979;Sears 1983;Sears and Valentino 1997). Correspondingly, the consistency and, hence, clarity of cue giving should vary across individuals and political topics.…”
Section: Family Circumstances Enhancing Parent-child Concordancementioning
confidence: 99%
“…According to the first approach, political attitudes and behaviours are acquired during early socialization and are resistant to change later in life (Easter et al, 2006;Sears and Funk, 1999;Sears and Valentino, 1997). Consequently, immigrants encounter many difficulties in adapting their political behaviour to the host society because they were socialized in a different context.…”
Section: Review Of Literature and Hypothesesmentioning
confidence: 99%